Let's complete steps 2 and 3 to solve the system of equations.
Given:
- \( y = 4x - 5 \)
- \( y = -3 \)
You've already substituted \( y = -3 \) into the first equation:
Step 2: Solve to determine the value of the unknown variable.
Substituting gives us the equation:
\[ -3 = 4x - 5 \]
Now, add 5 to both sides:
\[ -3 + 5 = 4x \]
This simplifies to:
\[ 2 = 4x \]
Now, divide both sides by 4:
\[ x = \frac{2}{4} = \frac{1}{2} \]
Step 3: Write the solution to the system of equations as an ordered pair.
We found \( x = \frac{1}{2} \) and we know \( y = -3 \).
Thus, the solution to the system is:
\[ \left( \frac{1}{2}, -3 \right) \]
So, the final solution to the system is:
The solution to the system is \(\left( \frac{1}{2}, -3 \right)\).